Multiple myeloma and kidney disease - Zarankiewicz, Natalia; Kosz, Katarzyna; Zielińska, Martyna; Remjasz, Klaudia; Kuchnicka, Aleksandra; Kuchnicka, Julia; Sapuła, Klaudia; Aleksandrowicz, Jakub; Siedlecki, Wojciech (Journal of Education, Health and Sport, 2022)
Abstract Background: Multiple myeloma is a clonal plasma cell neoplasm which affects 1% of all malignancies. In this article we reviewed epidemiology, symptoms with particular attention to renal failure and its manifestation in multiple myeloma (MM). Material and methods: This paper was based on medical articles collected in PubMed from 2001 to 2022, medical websites and books. The research has been done by looking through key words such as: „multiple myeloma”, „myeloma cast nephropathy”, „bortezomib”, „RANKL” Results: Multiple myeloma has indolent course and many patients present renal disorders at the moment of diagnosis. The use of novel therapies can reverse renal failure. Conclusions: Treatment of the patients with MM and kidney disease is challenging for health care professionals. Doctors have to adjust treatment to provide the best therapeutic effects.